The Role of Health Education in Improving Health Workers’ Knowledge of Mental Health Services For The Ederly - Lilik Djuari; Farhan Nurdiansyah; Natasya Nurvita Brilianti (Universitas Airlangga, 2026)
The proportion of elderly individuals in Indonesia is increasing and is projected to reach 19.9% by 2045. This growing elderly population may become a burden on families and communities if the elderly are not in optimal physical, psychological, social, and economic health. Health, social, and economic challenges can impact the psychological well-being of the elderly, leading to mental health issues among them. Public health centers are primary health facilities that serve elderly individuals directly. Therefore, it is essential for healthcare workers at public health centers to have the knowledge necessary to detect early mental health issues in the elderly to enable effective mental health service management, with the involvement of families and communities. This study employed a one-group pre-test and post-test design. The respondents were 40 healthcare workers from Trawas public health center in Mojokerto, East Java, Indonesia. Their knowledge of elderly mental health was assessed using a 10-question questionnaire administered before and after a health education intervention. The health education covered mental health issues in the elderly, early detection of mental health problems in the elderly, and the roles of family, community health volunteers, and public health center staff in providing mental health services for the elderly. The healthcare workers’ knowledge of elderly mental health had a median score of 5.5 (range: 3-7) before the health education intervention and 8 (range: 6-9) after the intervention. The Wilcoxon test yielded a p-value of <0.001, indicating a significant difference in knowledge levels before and after the health education intervention. In conclusion, health education effectively enhances public health center healthcare workers' knowledge of mental health in the elderly.